The Ultra Lord of the Ukraine Special Operations’ Agricultural Division: How memetic artifacts provides a foundation for the historical archiving of conflicts - Shane Tilton; Alisa Agozzino (Cogent Social Sciences)
This case study examines how social media accounts use memes and on-the-ground content to create a “real-time” and historical record of the events happening in Ukraine during the 2022 invasion of their country by Russian forces and their allies. Artifacts from the Ukrainian Memes Forces’ Twitter account (among others) provides the memetic artifacts of examination. The grounding of this case study is based on Stuart Hall’s “Readings” to assess how audiences would interpret these messages the memetic artifacts via Twitter and TikTok and using an analysis of the layers within the memes that pro-Russian and pro-Ukrainian content creators are producing. The general theme is that pro-Russian content creators are focusing their content on an internal audience under a theme of nationalistic pride, while pro-Ukraine content creators are focusing their content on external audiences under the themes of satire of Russian propaganda and global awareness of the war.